2003
DOI: 10.1242/jcs.00698
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous proliferative potential in regenerative adult newt cardiomyocytes

Abstract: ResultsNewt cardiomyocytes undergo DNA synthesis and mitosis in dissociated culture Adult newt cardiomyocytes were dissociated by proteolysis. Routinely, 40-60% of the cells obtained were cardiomyocytes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 47 publications
8
95
0
1
Order By: Relevance
“…These results uncovered a frequent re-entry into cell cycle of the p53 + lineage, suggesting more potent proliferative ability of this lineage and proliferative heterogeneity of cardiomyocytes in mice. This kind of proliferative heterogeneity of cardiomyocytes was discovered in newts and zebrafish (Bettencourt-Dias et al, 2003;Kikuchi et al, 2010). Our results implicate that this phenomenon is conserved in mammalian heart.…”
Section: Discussionsupporting
confidence: 74%
“…These results uncovered a frequent re-entry into cell cycle of the p53 + lineage, suggesting more potent proliferative ability of this lineage and proliferative heterogeneity of cardiomyocytes in mice. This kind of proliferative heterogeneity of cardiomyocytes was discovered in newts and zebrafish (Bettencourt-Dias et al, 2003;Kikuchi et al, 2010). Our results implicate that this phenomenon is conserved in mammalian heart.…”
Section: Discussionsupporting
confidence: 74%
“…We used the percentage of cardiomyocytes in M-phase, which shows conservation of regulatory mechanisms and duration (∼1.5 h) between species, tissues, and ages (34)(35)(36). To calculate the number of cardiomyocytes generated from M-phase activity, determined by H3P analysis, we used the previously determined duration of 1.8 ± 0.3 h in adult ventricular cardiomyocytes (21,37). To correct our results for nonproductive mitotic events (binucleation, polyploidization), we multiplied by the age-specific percentage of mononucleated and diploid cardiomyocytes (from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies indicated that adult amphibian and zebrafish cardiomyocytes undergo DNA synthesis and karyokinesis in response to injury at a frequency much greater than that seen in adult mammals (Bettencourt-Dias et al, 2003;Oberpriller and Oberpriller, 1974;Poss et al, 2002). The potential origins of proliferative cardiomyocytes could include undifferentiated progenitor cells, which were implicated in one report (Lepilina et al, 2006), or existing cardiomyocytes.…”
Section: Cardiomyocyte-intrinsic Programs For Natural Heart Regenerationmentioning
confidence: 99%